THE EFFECT OF WORK FLEXIBILITY AND WORKING CONDITIONS ON JOB SATISFACTION AND PERFORMANCE OF ONLINE OJEK DRIVERS IN SURABAYA - Wanodya, Aprillita Dian; Mujanah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to determine work flexibility and working conditions on job satisfaction and performance of online motorcycle taxi drivers in Surabaya. The method used is quantitative with explanatory research. The number of samples in this study was 100 with respondents being online motorcycle taxi drivers consisting of Grab, Gojek, Indriver and Maxim. Distribution of questionnaires and data collection through google forms. Data analysis technique using Smart PLS. The test results obtained work flexibility has a significant positive effect on job satisfaction of online motorcycle taxi drivers in Surabaya, Flexibility has a significant positive effect on performance, Working conditions have no significant effect on job satisfaction